Long Work Hours and the Wellbeing of Fathers and their Families - Stanton, D; Qu, L; Weston, R; Gray, M (My University, 2004)
The average hours worked by full-time employees in Australia have increased since the late 1970s. This, combined with increases in female labour force participation, has led to concerns about the impact of long work hours on family life. This paper explores the relationship between fathers' work hours, their own wellbeing and that of their families using data from the HILDA survey. Overall, satisfaction with work hours decreases as the number of hours worked increases beyond the standard working week. However, long hours are not necessarily, or even on average associated with pervasively lower wellbeing. Work hours are negatively related to only two of the thirteen measures of wellbeing examined. For fathers working very long hours, their satisfaction with their work hours is found to be very important to the relationship between work hours and wellbeing.
Australian Journal of Labour Economics
Keywords: Employment; Families -- Fathers; Health; Families; Employment -- Hours; Health -- Wellbeing; Families and relationships; Health and wellbeing; Labour market; Health; Families; Employment; Wellbeing; Fathers; Hours; Health and wellbeing; Families and relationships; Employment and unemployment